2023
DOI: 10.6004/jnccn.2023.70012
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analyses in AML: What Have We Learned, How Should This Impact Patient Care, and What Needs to Be Done in the Future?

Abstract: Acute myeloid leukemia (AML) is the most common acute leukemia in adults in the United States and has seen the approval of several novel agents over the past decade. Similar to treatments for other hematologic and solid malignancies, these novel agents are costly. In the setting of finite financial resources in the healthcare system, the concept of cost-effectiveness analyses has been developed to compare the estimated costs and associated benefits expected with different interventions (eg, drugs, diagnostic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The past decades have been marked by an increasing progress in the scientific understanding of AML biology, leading to enhanced prognostication tools and risk assessments [ 5 , 29 ]. Due to a combination of advances in supportive care and the availability of novel, often molecularly targeted, therapies, the life expectancy of AML patients continues to improve [ 30 , 31 ]. However, despite obvious progress in the diagnosis and management of AML, some obstacles in the successful achievement of the therapy response exist, one of which is the initial resistance of leukemic cells to cytotoxic drugs [ 3 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The past decades have been marked by an increasing progress in the scientific understanding of AML biology, leading to enhanced prognostication tools and risk assessments [ 5 , 29 ]. Due to a combination of advances in supportive care and the availability of novel, often molecularly targeted, therapies, the life expectancy of AML patients continues to improve [ 30 , 31 ]. However, despite obvious progress in the diagnosis and management of AML, some obstacles in the successful achievement of the therapy response exist, one of which is the initial resistance of leukemic cells to cytotoxic drugs [ 3 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acute myeloid leukemia (AML) is a genetically heterogeneous disease, characterized by abnormal hematopoiesis, differentiation blockade and inadequate production of blood cells 1 , 2 . It is the most common myeloid leukemia in adults 3 , 4 . Previous research in our laboratory have shown that the prognosis of AML is closely related to immune checkpoints 5 - 7 .…”
Section: Introductionmentioning
confidence: 99%